2017
DOI: 10.1371/journal.pone.0178739
|View full text |Cite
|
Sign up to set email alerts
|

One bout of open skill exercise improves cross-modal perception and immediate memory in healthy older adults who habitually exercise

Abstract: One single bout of exercise can be associated with positive effects on cognition, due to physiological changes associated with muscular activity, increased arousal, and training of cognitive skills during exercise. While the positive effects of life-long physical activity on cognitive ageing are well demonstrated, it is not well established whether one bout of exercise is sufficient to register such benefits in older adults. The aim of this study was to test the effect of one bout of exercise on two cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 66 publications
2
49
0
3
Order By: Relevance
“…A benefit of one bout of exercise on multisensory processing, (i.e., the ability to appropriately integrate information from different sensory modalities), has been demonstrated in the elderly [43], but there is also the need to better investigate this cognitive ability in children, as it represents a foundation to learning and cognitive development [44].…”
Section: Discussionmentioning
confidence: 99%
“…A benefit of one bout of exercise on multisensory processing, (i.e., the ability to appropriately integrate information from different sensory modalities), has been demonstrated in the elderly [43], but there is also the need to better investigate this cognitive ability in children, as it represents a foundation to learning and cognitive development [44].…”
Section: Discussionmentioning
confidence: 99%
“…During this specific mid-intervention we will monitor the amount of PA performing an active break, 10 min thrice a day, during a school day for a week. This assessment will be focused on cognitive function and time-on-task behaviors, since these could be more affected after acute exercises than chronic ones, as shown for some cognitive functions in the literature [24][25][26]. The time spent on physical activity and sedentary behavior will be calculated through actigraph accelerometers (ActiLife6 wGT3X-BT).…”
Section: Data Collection and Outcome Measuresmentioning
confidence: 99%
“…In the present study, we built on O'Brien et al (2017), and we hypothesised that an acute bout of exercise will facilitate cognitive performance in school aged children.…”
Section: Smithmentioning
confidence: 99%
“…In a study with an older population (O'Brien et al 2017), we tested adults aged 60+ before and after one bout of open-or closed-skill exercise and compared their performance with a control group of participants who took part in a reading club for one session of the same time length. Results showed that immediate memory, assessed with the Digit Span forward test, improved after both exercise types, while benefits on multisensory perception, assessed with the Sound-Induced Flash Illusion (SIFI) (Shams et al 2000), were found only for the open-skill group.…”
Section: Introductionmentioning
confidence: 99%